2019
DOI: 10.1007/s00270-019-02200-1
|View full text |Cite
|
Sign up to set email alerts
|

Local Ultrasound-Facilitated Thrombolysis in High-Risk Pulmonary Embolism: First Dutch Experience

Abstract: Purpose To provide insight into the current use and results of ultrasound-facilitated catheter-directed thrombolysis (USAT) in patients with high-risk pulmonary embolism (PE). Introduction Systemic thrombolysis is an effective treatment for hemodynamically unstable, high-risk PE, but is associated with bleeding complications. USAT is thought to reduce bleeding and is therefore advocated in patients with high-risk PE and contraindications for systemic thrombolysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…This is further illustrated by our previously published case series of high-risk PE patients, in which ICH following CDT treatment with the EKOS catheter only occurred in two patients, both of whom had absolute contraindications for thrombolytic therapy (i.e. concurrent ischaemic stroke and recent subarachnoid haemorrhage) 20 …”
Section: Catheter-based Therapies In High-risk Pulmonary Embolism Patmentioning
confidence: 80%
See 1 more Smart Citation
“…This is further illustrated by our previously published case series of high-risk PE patients, in which ICH following CDT treatment with the EKOS catheter only occurred in two patients, both of whom had absolute contraindications for thrombolytic therapy (i.e. concurrent ischaemic stroke and recent subarachnoid haemorrhage) 20 …”
Section: Catheter-based Therapies In High-risk Pulmonary Embolism Patmentioning
confidence: 80%
“…showed that CDT is an effective alternative in patients with failed ST, leading to improvement of clinical outcomes and echocardiographic parameters at a low complication rate. Results from our registry indicate that high-risk PE patients who underwent both ST and CDT with the EKOS catheter had a higher mortality in general but similar incidence of major and fatal bleeding compared to patients who received CDT only 20 . This suggests that patient’s clinical condition is most threatened by haemodynamic instability due to PE rather than bleeding, reflecting the underlying severe disease requiring intensive treatment, such as emergency CDT.…”
Section: Catheter-based Therapies In High-risk Pulmonary Embolism Patmentioning
confidence: 88%
“…More recently, deWinter and colleagues analyzed all the high‐risk PE treated in the Netherlands with CDL; in a total of 33 patients bleeding occurred in 12 patients, including one intracranial and three fatal bleeding episodes. The mortality at 1 month was 48% 14 . Despite the relatively low dose of thrombolytics used with CDL, major bleeding complications pooled to 5.4% in a recent meta‐analysis 15 .…”
Section: Discussionmentioning
confidence: 99%
“…[200][201][202][203][204] Catheter-directed approaches allow the use of a considerably lower dose of thrombolytics (~1/10 as compared to systemic treatment), thus these type of procedures are possibly associated with a lower risk of bleeding. 198,203,205 However, data for this therapy is still evolving and it cannot be used in high-risk PE and severely compromised patients, unless intravenous thrombolysis is contraindicated or failed. In high-risk patients with contraindications for systemic treatment, although guidelines may advocate the use of catheter-directed thrombolysis, caution is warranted in patient selection because of the high incidence of major bleeding and mortality in this population.…”
Section: Mechanical Thrombectomy For Patients With Ais and Tpmentioning
confidence: 99%